On the Future of Environmental Economics - Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1999)
Environmental economics passed its age of infancy. It grew rapidly over the last decades and established itself as a discipline based on the powerful economic paradigm and reaching beyond it to capture important economy-environment interactions. The view offered here on the future of environmental economics is based on the premise that economic pressures will tend to put the ecological system under increasing stress and will thus geopardize the sustainable development of both the economic and the ecological system, unless the understanding of the economy-environment interdependence is further improved and all agents in the political decision making process can be convinced to take the necessary political action. The paper does not discuss the major likely, promising and/or necessary substantive topics on the agenda of future research in a systematic way. It chooses, instead, the methods of analysis as the primary organizing principle starting out from theoretical concepts (externality theory) and their ramifications then turning to issues of interdisciplinarity and empirical relevance to finally assess the (future) impact of environmental economics on shaping environmental policy. Real-world environmental problems, the driving forces of research in the field, are also addressed, of course, but under the premise that there is not too much dispute about what the relevant issues are. Attention is drawn on a number of current deficits and proposals for improvement are offered. Given the recent thriving expansion of the field and its increasing impact on practical environmental policy, there is little reason to believe that this positive development will not continue. But if additional efforts are directed towards coping with the current weaknesses identified in the paper environmental economists will certainly be able to do even better than in the past.
Keywords: 330